Perancangan Sistem Manajemen Pengarsipan Data - Dirga Setia Fahreza; Agus Budiyantara (Repeater : Publikasi Teknik Informatika dan Jaringan, 2025)
The development of digital era technology is currently so rapid that all kinds of human activities are very dependent on technological advances. Digitalization has penetrated all sectors of modern human life, including data archiving activities. Archives are very important for an organization or government if the archives are managed properly and correctly. Because the completeness of data and information really depends on the archiving system. The aim of this research is to determine the effect of implementing digital archives for storing digital documents. This type of research uses a qualitative approach. This qualitative research seeks to explore and understand different truths by different people. In a qualitative approach, one type of approach that is often used is the case study approach. The data analysis technique used is an interactive model data analysis technique. The results of this research explain the effects of implementing digital archives for storing digital documents.